MUCILAGE-RELATED10 Produces Galactoglucomannan That Maintains Pectin and Cellulose Architecture in Arabidopsis Seed Mucilage. Issue 1 (28th July 2015) - Voiniciuc, Cătălin; Schmidt, Maximilian Heinrich-Wilhelm; Berger, Adeline; Yang, Bo; Ebert, Berit; Scheller, Henrik V.; North, Helen M.; Usadel, Björn; Günl, Markus
Abstract : A highly branched polymer defines the distribution of pectin and the structure of cellulose in Arabidopsis mucilage. Abstract: Plants invest a lot of their resources into the production of an extracellular matrix built of polysaccharides. While the composition of the cell wall is relatively well characterized, the functions of the individual polymers and the enzymes that catalyze their biosynthesis remain poorly understood. We exploited the Arabidopsis ( Arabidopsis thaliana ) seed coat epidermis (SCE ) to study cell wall synthesis. SCE cells produce mucilage, a specialized secondary wall that is rich in pectin, at a precise stage of development. A coexpression search for MUCILAGE - RELATED ( MUCI ) genes identified MUCI10 as a key determinant of mucilage properties. MUCI10 is closely related to a fenugreek ( Trigonella foenumgraecum ) enzyme that has in vitro galactomannan α-1, 6-galactosyltransferase activity. Our detailed analysis of the muci10 mutants demonstrates that mucilage contains highly branched galactoglucomannan (GGM ) rather than unbranched glucomannan. MUCI10 likely decorates glucomannan, synthesized by CELLULOSE SYNTHASE-LIKE A2, with galactose residues in vivo. The degree of galactosylation is essential for the synthesis of the GGM backbone, the structure of cellulose, mucilage density, as well as the adherence of pectin. We propose that GGM scaffolds control mucilage architecture along with cellulosic rays and show that Arabidopsis SCE cells represent an excellent model in which to study the synthesis and function of GGM . Arabidopsis natural varieties with defects similar to muci10 mutants may reveal additional genes involved in GGM synthesis. Since GGM is the most abundant hemicellulose in the secondary walls of gymnosperms, understanding its biosynthesis may facilitate improvements in the production of valuable commodities from softwoods.